Preparation method of hydrophobic silica aerogel and application thereof

CN121317776BActive Publication Date: 2026-10-16SHANDONG PEAK-TECH NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511724116.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-22
Publication Date
2026-10-16
Estimated Expiration
2045-11-22

AI Technical Summary

Technical Problem

[0003]公开号为CN108290741A的中国发明专利申请公开了二氧化硅气凝胶的制备方法和由其制备的二氧化硅气凝胶,该发明使用第一水玻璃溶液形成第一二氧化硅湿凝胶,然后另外添加第二水玻璃溶液,形成具有提高的物理性能的二氧化硅气凝胶,分别控制第一水玻璃溶液和第二水玻璃溶液中二氧化硅的浓度,制备具有特定的振实密度和可控密度的二氧化硅气凝胶,但其力学性能有待提高

Benefits of technology

[0020]由于采用以上技术方案,本发明的有益效果包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a preparation method of hydrophobic silica aerogel and application thereof, and relates to the technical field of silica preparation. The preparation method of the hydrophobic silica aerogel comprises the following steps: uniformly stirring and mixing anhydrous ethanol, deionized water, a silicon source and modified silane, adding an acid catalyst, performing temperature rising hydrolysis, adding an ammonia water solution, and aging to obtain a gel; and performing solvent replacement on the gel, and drying to obtain the hydrophobic silica aerogel. The hydrophobic silica aerogel prepared by the method has low density and heat conductivity, good compression strength and hydrophobic performance, and has a good application prospect in the field of heat insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silica preparation technology, specifically to a method for preparing hydrophobic silica aerogel and its application. Background Technology

[0002] Silica aerogel, with its three-dimensional porous network structure, possesses numerous excellent properties such as high porosity, high specific surface area, and low thermal conductivity, making it a high-performance novel thermal insulation material widely used in the thermal protection of aerospace vehicles and missiles, as well as in the thermal insulation of military thermal batteries and ramjet engines. However, traditional silica aerogels suffer from poor mechanical strength, and their structure is easily damaged, significantly reducing their thermal insulation performance. Furthermore, the silica framework structure is easily destroyed by absorbing moisture from the air, further affecting its thermal insulation properties. These drawbacks greatly limit the practical applications of silica aerogels. Therefore, developing a silica aerogel with good mechanical properties and hydrophobic properties is currently a research hotspot in this field.

[0003] Chinese invention patent application CN108290741A discloses a method for preparing silica aerogel and the silica aerogel prepared therefrom. This invention uses a first water glass solution to form a first silica wet gel, and then adds a second water glass solution to form a silica aerogel with improved physical properties. The concentration of silica in the first water glass solution and the second water glass solution are controlled respectively to prepare silica aerogel with specific tap density and controllable density, but its mechanical properties need to be improved. Summary of the Invention

[0004] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a method for preparing hydrophobic silica aerogel and its application.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing hydrophobic silica aerogel includes the following steps: (1) Mix anhydrous ethanol, deionized water, silicon source and modified silane, add acid catalyst, heat and hydrolyze, add ammonia solution, age to obtain gel; (2) The gel was solvent-displaced and dried to obtain a hydrophobic silica aerogel;

[0006] The modified silane is prepared by the following method:

[0007] S1: p-Phenylenediamine reacts with hydroxyethyl acrylate to form a four-armed compound, and the reaction equation is shown below:

[0008] S2: The four-armed compound reacts with L-lactide to form a four-armed polyester compound, and the reaction equation is shown below:

[0009] S3: The four-armed polyester compound reacts with methacrylic anhydride to generate terminal alkenyl polyesters, and the reaction equation is shown below:

[0010] S4: Terminal alkenyl polyester reacts with γ-aminopropylmethyldiethoxysilane to generate modified silane, and the reaction equation is shown below:

[0011] In step S1, the molar ratio of p-phenylenediamine to hydroxyethyl acrylate is 1:(4.05-4.1).

[0012] In step S2, the molar ratio of the four-armed compound to L-lactide is 1:(16-24).

[0013] In step S3, the molar ratio of the four-armed polyester compound to methacrylic anhydride is 1:(4.1-4.2).

[0014] In step S4, the molar ratio of the terminal alkenyl polyester to γ-aminopropylmethyldiethoxysilane is 1:(4.05-4.1).

[0015] In step (1), the silicon source is a mixture of methyltriethoxysilane and ethyl silicate; the mass ratio of methyltriethoxysilane, ethyl silicate and modified silane is (0.5-1):1:(0.2-0.5).

[0016] In step (1), the acid catalyst is oxalic acid.

[0017] In step (1), the temperature for hydrolysis is 40-50℃.

[0018] In step (1), the aging temperature is 20-40℃.

[0019] Application of a hydrophobic silica aerogel in thermal insulation.

[0020] Due to the adoption of the above technical solutions, the beneficial effects of the present invention include: The hydrophobic silica aerogel prepared by this invention has low density and thermal conductivity, good compressive strength and hydrophobic properties, and has good application prospects in the field of thermal insulation. Detailed Implementation

[0021] The following description, in conjunction with specific embodiments, provides further details, but the present invention is not limited to these embodiments.

[0022] Example 1: Preparation of modified silanes: S1: Under nitrogen protection, 300 ml of methanol, 0.1 mol of p-phenylenediamine, and 0.01 mol of hydroquinone were added to a reaction vessel and stirred until homogeneous. The mixture was heated to 40 °C, and 0.405 mol of hydroxyethyl acrylate was added dropwise over 30 min. The mixture was then refluxed for 8 h, cooled to 40 °C, and distilled under reduced pressure for 1 h. 200 ml of cold diethyl ether was added and stirred to precipitate the precipitate. The precipitate was filtered, washed with 100 ml of cold diethyl ether, and dried under vacuum at 50 °C for 10 h to obtain the four-armed compound. Its 1H NMR data are as follows: 1 H NMR (300 MHz, DMSO-d6) δ 7.21(s, 4H), 4.65 (t, J = 6.4 Hz, 4H), 4.17 (t, J = 5.0 Hz, 8H), 3.80 (dt, J =6.4, 5.0 Hz, 8H), 3.65 (s, 4H), 2.89 (d, J = 13.2 Hz, 8H), 2.55 (t, J = 6.5Hz, 8H); S2: Under nitrogen protection, 1000 ml of anhydrous THF, 0.1 mol of the four-armed compound, 1.6 mol of L-lactide, and 2 g of stannous octoate were added to a reaction vessel. The mixture was stirred and heated to 50 °C. Under stirring, the mixture was evacuated for 1 h to remove THF. The reaction vessel was sealed, and the temperature was raised to 100 °C. The reaction was carried out for 20 h. After cooling to room temperature, 600 ml of chloroform was added and stirred until homogeneous. 1000 ml of methanol was slowly added and stirred to precipitate the precipitate. The precipitate was filtered and dried under vacuum at 50 °C for 10 h to obtain the four-armed polyester compound with a number-average molecular weight of 2904. Its 1H NMR data are as follows: 1 H NMR (300 MHz, Chloroform-d) δ 7.21 (s, 4H), 5.41 (q, J = 6.4 Hz, 24H), 5.33 (d, J = 6.7 Hz, 4H), 4.38 - 4.19 (m, 20H), 3.62 (s, 4H), 3.17 (d,J = 5.6 Hz, 4H), 2.92 (t, J = 6.6 Hz, 8H), 2.55 (t, J = 6.6 Hz, 8H), 1.42 -1.30 (m, 96H); S3: Under nitrogen protection, 300 ml of THF, 0.01 mol of the four-armed polyester compound, and 1 mmol of hydroquinone were added to a reaction vessel and stirred until homogeneous. The mixture was heated to 40 °C, and 50 ml of a THF solution containing 0.041 mol of methacrylic anhydride was added dropwise over 30 min. The mixture was then refluxed for 8 h, cooled to room temperature, and distilled under reduced pressure at 40 °C for 1 h. 150 ml of methanol was added and stirred to precipitate a solid. The solid was filtered, washed with 50 ml of methanol, and dried under vacuum at 50 °C for 10 h to obtain a terminal alkenyl polyester with a number-average molecular weight of 3176. Its 1H NMR data are as follows: 1 H NMR (300 MHz, Chloroform-d) δ 7.21 (s, 4H), 5.80 (dt, J = 1.8, 0.9Hz, 4H), 5.58 (dd, J = 2.0, 1.3 Hz, 4H), 5.45 - 5.28 (m, 32H), 4.33 (d, J =1.2 Hz, 16H), 3.62 (s, 4H), 2.92 (t, J = 6.6 Hz, 8H), 2.55 (t, J = 6.6 Hz,8H), 1.95 - 1.89 (m, 12H), 1.38 (dd, J = 7.0, 4.7 Hz, 96H); S4: Under nitrogen protection, 350 ml THF, 0.01 mol terminal alkenyl polyester, 0.0405 mol γ-aminopropylmethyldiethoxysilane, and 1 mmol hydroquinone were added to a reaction vessel, stirred and mixed, heated to 40 °C, and reacted for 26 h. The mixture was then distilled under reduced pressure for 1 h, and 150 ml methanol was added and stirred to precipitate a solid. The solid was filtered, washed with 100 ml methanol, and dried under vacuum at 50 °C for 10 h to obtain the modified silane. Its 1H NMR data are as follows: 1 H NMR (300 MHz, Chloroform-d) δ 7.21 (s, 4H), 5.47 -5.25 (m, 32H), 4.33 (s, 18H), 3.76 (q, J = 7.2 Hz, 16H), 3.62 (s, 4H), 3.53(tt, J = 5.9, 4.4 Hz, 2H), 3.02 - 2.88 (m, 10H), 2.76 - 2.48 (m, 28H), 1.59 -1.31 (m, 104H), 1.19 - 1.01 (m, 30H), 0.80 (t, J = 8.8 Hz, 8H), 0.13 (s,12H).

[0023] Example 2: Preparation of modified silanes: S1: Under nitrogen protection, 300 ml of methanol, 0.1 mol of p-phenylenediamine, and 0.01 mol of hydroquinone were added to a reaction vessel and stirred until homogeneous. The mixture was heated to 45 °C, and 0.408 mol of hydroxyethyl acrylate was added dropwise over 30 min. The mixture was then refluxed for 9 h, cooled to 40 °C, and distilled under reduced pressure for 1 h. 200 ml of cold diethyl ether was added and stirred to precipitate the precipitate. The precipitate was filtered, washed with 100 ml of cold diethyl ether, and dried under vacuum at 50 °C for 10 h to obtain the four-armed compound. S2: Under nitrogen protection, 1000 ml of anhydrous THF, 0.1 mol of the four-armed compound, 2 mol of L-lactide, and 2 g of stannous octoate were added to a reaction vessel, stirred, and heated to 50 °C. Under stirring, the vessel was evacuated for 1 h to remove THF. The reaction vessel was sealed, heated to 105 °C, and reacted for 18 h. After cooling to room temperature, 600 ml of chloroform was added, stirred, and mixed. 1000 ml of methanol was slowly added and stirred to precipitate the precipitate. The precipitate was filtered and dried under vacuum at 50 °C for 10 h to obtain the four-armed polyester compound with a number-average molecular weight of 3480. S3: Under nitrogen protection, 300 ml THF, 0.01 mol of the tetra-armed polyester compound, and 1 mmol of hydroquinone were added to the reaction vessel and stirred until homogeneous. The mixture was heated to 45 °C, and 50 ml of a THF solution containing 0.0415 mol of methacrylic anhydride was added dropwise over 30 min. The mixture was then refluxed for 7 h, cooled to room temperature, and distilled under reduced pressure at 40 °C for 1 h. 150 ml of methanol was added and stirred to precipitate the solid. The solid was filtered, washed with 50 ml of methanol, and dried under vacuum at 50 °C for 10 h to obtain the terminal alkenyl polyester with a number-average molecular weight of 3752. S4: Under nitrogen protection, 350 ml THF, 0.01 mol terminal alkenyl polyester, 0.0408 mol γ-aminopropylmethyldiethoxysilane, and 1 mmol hydroquinone were added to a reaction vessel, stirred and mixed, heated to 45 °C, reacted for 25 h, distilled under reduced pressure for 1 h, added 150 ml methanol and stirred to precipitate solid, filtered, washed with 100 ml methanol, and dried under vacuum at 50 °C for 10 h to obtain modified silane.

[0024] Example 3: Preparation of modified silanes: S1: Under nitrogen protection, 300 ml of methanol, 0.1 mol of p-phenylenediamine, and 0.01 mol of hydroquinone were added to a reaction vessel and stirred until homogeneous. The mixture was heated to 50 °C, and 0.41 mol of hydroxyethyl acrylate was added dropwise over 30 min. The mixture was then refluxed for 10 h, cooled to 40 °C, and distilled under reduced pressure for 1 h. 200 ml of cold diethyl ether was added and stirred to precipitate the precipitate. The precipitate was filtered, washed with 100 ml of cold diethyl ether, and dried under vacuum at 50 °C for 10 h to obtain the four-armed compound. S2: Under nitrogen protection, 1000 ml of anhydrous THF, 0.1 mol of the four-armed compound, 2.4 mol of L-lactide, and 2 g of stannous octoate were added to a reaction vessel, stirred, and heated to 50 °C. Under stirring, the vessel was evacuated for 1 h to remove THF. The reaction vessel was then sealed, heated to 110 °C, and reacted for 24 h. After cooling to room temperature, 600 ml of chloroform was added, and the mixture was stirred until homogeneous. 1000 ml of methanol was slowly added and stirred to precipitate the precipitate. The precipitate was filtered and dried under vacuum at 50 °C for 10 h to obtain the four-armed polyester compound with a number-average molecular weight of 4056. S3: Under nitrogen protection, 300 ml THF, 0.01 mol of the four-armed polyester compound, and 1 mmol of hydroquinone were added to the reaction vessel and stirred until homogeneous. The mixture was heated to 50 °C, and 50 ml of THF solution containing 0.042 mol of methacrylic anhydride was added dropwise over 30 min. The mixture was then refluxed for 6 h, cooled to room temperature, and distilled under reduced pressure at 40 °C for 1.5 h. 150 ml of methanol was added and stirred to precipitate the solid. The solid was filtered, washed with 50 ml of methanol, and dried under vacuum at 50 °C for 10 h to obtain the terminal alkenyl polyester with a number average molecular weight of 4328. S4: Under nitrogen protection, 350 ml THF, 0.01 mol terminal alkenyl polyester, 0.041 mol γ-aminopropylmethyldiethoxysilane, and 1 mmol hydroquinone were added to a reaction vessel, stirred and mixed, heated to 50 °C, reacted for 24 h, distilled under reduced pressure for 1 h, added 150 ml methanol and stirred to precipitate solid, filtered, washed with 100 ml methanol, and dried under vacuum at 50 °C for 10 h to obtain modified silane.

[0025] Example 4: Preparation of hydrophobic silica aerogel: (1) Add 280ml anhydrous ethanol, 20ml deionized water, 5g methyltriethoxysilane, 10g ethyl silicate, and 2g modified silane (prepared in Example 1) to a reaction vessel, stir for 30min, add 2g oxalic acid, stir for 30min, heat to 40℃, hydrolyze for 7h, add 5g 25wt% ammonia solution, stir for 10min, cool to 20℃, pour into a 10cm×10cm×10cm mold, and let stand and seal for aging for 24h to obtain a gel; (2) The gel was immersed in 500 ml of n-hexane for solvent replacement. The solvent was replaced every 4 hours for a total of 3 times, each time using 500 ml of n-hexane. The gel was dried at 60°C for 24 hours to obtain hydrophobic silica aerogel.

[0026] Example 5: Preparation of hydrophobic silica aerogel: (1) Add 280ml anhydrous ethanol, 20ml deionized water, 8g methyltriethoxysilane, 10g ethyl silicate, and 4g modified silane (prepared in Example 2) to a reaction vessel, stir for 30min, add 4g oxalic acid, stir for 30min, heat to 45℃, hydrolyze for 7h, add 8g 25wt% ammonia solution, stir for 10min, cool to 30℃, pour into a 10cm×10cm×10cm mold, and let stand and seal for aging for 28h to obtain a gel; (2) The gel was immersed in 500 ml of n-hexane for solvent replacement. The solvent was replaced every 4 hours for a total of 3 times, each time using 500 ml of n-hexane. The gel was dried at 70°C for 20 hours to obtain hydrophobic silica aerogel.

[0027] Example 6: Preparation of hydrophobic silica aerogel: (1) Add 280ml anhydrous ethanol, 20ml deionized water, 10g methyltriethoxysilane, 10g ethyl silicate, and 5g modified silane (prepared in Example 3) to a reaction vessel, stir for 30min, add 5g oxalic acid, stir for 30min, heat to 50℃, hydrolyze for 6h, add 5-10g 25wt% ammonia solution, stir for 10min, cool to 40℃, pour into a 10cm×10cm×10cm mold, let stand and seal for aging for 24h to obtain gel; (2) The gel was immersed in 500 ml of n-hexane for solvent replacement. The solvent was replaced every 4 hours for a total of 3 times, each time using 500 ml of n-hexane. The gel was dried at 80°C for 18 hours to obtain hydrophobic silica aerogel.

[0028] Comparative Example 1 The preparation method of the hydrophobic silica aerogel is basically the same as that in Example 5, except that the modified silane used in step (1) is replaced with an equal weight of the modified silane prepared by the following method: The preparation method of the modified silane is basically the same as that in Example 2, except that the p-phenylenediamine in step S1 is replaced with an equimolar amount of 1,6-hexanediamine.

[0029] Comparative Example 2 The preparation method of the hydrophobic silica aerogel is basically the same as that in Example 5, except that the modified silane used in step (1) is replaced with an equal weight of the modified silane prepared by the following method: The preparation method of the modified silane is basically the same as that in Example 2, except that the amount of hydroxyethyl acrylate added in step S1 is replaced with 0.204 mol, the amount of L-lactide added in step S2 is replaced with 1 mol, the amount of methacrylic anhydride added in step S3 is replaced with 0.021 mol, and the amount of γ-aminopropylmethyldiethoxysilane added in step S4 is replaced with 0.0202 mol.

[0030] Comparative Example 3 The preparation method of the hydrophobic silica aerogel is basically the same as that in Example 5, except that the modified silane used in step (1) is replaced with an equal weight of the modified silane prepared by the following method: The preparation method of the modified silane is basically the same as that in Example 2, except that L-lactide in step S2 is replaced with an equimolar amount of 6-caprolactone.

[0031] Comparative Example 4 The preparation method of the hydrophobic silica aerogel is basically the same as that in Example 5, except that the modified silane used in step (1) is replaced with an equal weight of the modified silane prepared by the following method: The preparation method of the modified silane is basically the same as that in Example 2, except that the γ-aminopropylmethyldiethoxysilane in step S4 is replaced with an equimolar amount of 3-aminopropyltriethoxysilane.

[0032] The hydrophobic silica aerogel samples prepared in Examples 4-6 and Comparative Examples 1-4 of this application were tested for density, compressive strength, thermal insulation and hydrophobic properties. The test results are shown in Table 1.

[0033] Sample preparation: Under the conditions of 25°C and 45% humidity, the hydrophobic silica aerogels prepared in the examples and comparative examples were cut into 5cm×5cm×5cm samples. The upper and lower surfaces were polished smooth with 600-grit sandpaper and kept parallel.

[0034] Density test: Under conditions of 25℃ and 45% humidity, accurately weigh the sample by mass m, seal the sample with wax, and measure the sample volume V using the water displacement method (place the sealed sample in a beaker filled with deionized water; the volume of water that overflows is the sample volume). Calculate the apparent density using the following formula:

[0035] Compressive strength test: Use a WDW-05 universal testing machine to compress the sample to a height of 2.5 cm (50% compression deformation), record the stress F experienced by the sample, and calculate the compressive strength using the following formula:

[0036] Where S is the pressure-bearing area of ​​the aerogel sample being tested, in mm². 2 .

[0037] Thermal insulation performance test: The thermal conductivity of the sample was tested using a TC3200 thermal conductivity meter.

[0038] Hydrophobicity test: 2µL of deionized water was dropped onto the sample surface, and the surface water contact angle was measured using the DropMeter A-200 contact angle system.

[0039] Table 1 Performance Test Data

[0040] As can be seen from the data in Examples 4, 5, and 6 in Table 1, the hydrophobic silica aerogel prepared by the present invention has low density and thermal conductivity, good compressive strength and hydrophobic properties, and has good application prospects in the field of thermal insulation.

[0041] The modified silane used in the preparation of hydrophobic silica aerogels in this application has a four-arm structure containing silyl ethoxy groups, polyester segments, and benzene rings. The silyl ethoxy group hydrolyzes to silanol (-Si-OH) under acidic conditions, and then undergoes condensation polymerization with methyltriethoxysilane and the hydrolysis products of ethyl silicate CH3-Si(OH)3 or Si(OH)4 under alkaline conditions to form siloxane (Si-O-Si) covalent bonds, thereby improving the interfacial bonding force between the modified silane and silica. The four-arm structure of the modified silane provides steric hindrance, preventing excessive aggregation of silica particles, increasing the porosity of the aerogel, and reducing its density. The polyester segments can absorb and disperse stress through rotation and conformational changes, effectively preventing the rapid propagation of microcracks, allowing the aerogel to withstand certain external forces without pulverizing. Furthermore, the polyester segments synergistically work with the four-arm structure to form an interpenetrating network structure, reducing interfacial slippage during compression. The rigid benzene ring enables efficient stress transfer, reduces local stress concentration, and acts as a molecular pillar to resist bending deformation under compressive stress. In Comparative Example 3, the modified silane used contained polycaprolactone segments, whose flexibility reduced stress transfer efficiency and decreased compressive strength. In Comparative Example 4, the modified silane contained three silylethoxy groups, which enabled higher crosslinking density, resulting in a denser gel network, increased aerogel density, and decreased thermal insulation performance.

[0042] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing hydrophobic silica aerogel, characterized in that, Includes the following steps: (1) Mix anhydrous ethanol, deionized water, silicon source and modified silane, add acid catalyst, heat and hydrolyze, add ammonia solution, age to obtain gel; (2) The gel was solvent-displaced and dried to obtain a hydrophobic silica aerogel; In step (1), the silicon source is a mixture of methyltriethoxysilane and ethyl silicate; The modified silane is prepared by the following method: S1: p-Phenylenediamine reacts with hydroxyethyl acrylate to form a four-armed compound. S2: The four-armed compound reacts with L-lactide to form a four-armed polyester compound. S3: A tetra-armed polyester compound reacts with methacrylic anhydride to form a terminal alkenyl polyester. S4: Terminal alkenyl polyester reacts with γ-aminopropylmethyldiethoxysilane to generate modified silane.

2. The method for preparing a hydrophobic silica aerogel according to claim 1, characterized in that, In step S1, the molar ratio of p-phenylenediamine to hydroxyethyl acrylate is 1:(4.05-4.1).

3. The method for preparing a hydrophobic silica aerogel according to claim 1, characterized in that, In step S2, the molar ratio of the four-armed compound to L-lactide is 1:(16-24).

4. The method for preparing a hydrophobic silica aerogel according to claim 1, characterized in that, In step S3, the molar ratio of the four-armed polyester compound to methacrylic anhydride is 1:(4.1-4.2).

5. The method for preparing a hydrophobic silica aerogel according to claim 1, characterized in that, In step S4, the molar ratio of the terminal alkenyl polyester to γ-aminopropylmethyldiethoxysilane is 1:(4.05-4.1).

6. The method for preparing a hydrophobic silica aerogel according to claim 1, characterized in that, The mass ratio of methyltriethoxysilane, ethyl silicate and modified silane is (0.5-1):1:(0.2-0.5).

7. The method for preparing a hydrophobic silica aerogel according to claim 1, characterized in that, In step (1), the acid catalyst is oxalic acid.

8. The method for preparing a hydrophobic silica aerogel according to claim 1, characterized in that, In step (1), the temperature for hydrolysis is 40-50℃.

9. The method for preparing a hydrophobic silica aerogel according to claim 1, characterized in that, In step (1), the aging temperature is 20-40℃.

10. The application of a hydrophobic silica aerogel prepared by the preparation method according to any one of claims 1-9 in thermal insulation.

Citation Information

Patent Citations

  • Method for manufacturing silica aerogel and silica aerogel manufactured thereby

    CN108290741A

  • Preparation method of super-hydrophobic silicon dioxide aerogel microspheres

    CN113816386A

  • Nano silicon dioxide sol and preparation method thereof

    CN120518085A